2010
DOI: 10.2478/s11658-010-0027-z
|View full text |Cite
|
Sign up to set email alerts
|

Leptin regulates MMP-2, TIMP-1 and collagen synthesis via p38 MAPK in HL-1 murine cardiomyocytes

Abstract: Abbreviations used: AP-1 -activator protein-1; ATF-2 -activating transcription factor-2; ECM -extracellular matrix; HF-heart failure; LV -left ventricular; MAPK -mitogen activated protein kinase; MMP -matrix metalloproteinase; mRNA-messenger ribonucleic acid; PBS -phosphate buffered saline; PCR -polymerase chain reaction; TIMP-tissue inhibitor of metalloproteinase Abstract: A clear association between obesity and heart failure exists and a significant role for leptin, the product of the obese gene, has been su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 35 publications
3
40
0
2
Order By: Relevance
“…Tolylsam treatment was associated with significantly reduced levels of leptin, which correlate positively with body fat mass and adipocyte size [5,18]. Leptin contributes to enhanced MMP-2 levels in different cell types [7][8][9][10][11][12]. In vascular smooth muscle cells leptin induces MMP-2 expression via protein kinase C-dependent activation of NAD(P)H oxidase with subsequent activation of the ERK1/2/NF-kappa B pathways [8].…”
Section: Metabolic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Tolylsam treatment was associated with significantly reduced levels of leptin, which correlate positively with body fat mass and adipocyte size [5,18]. Leptin contributes to enhanced MMP-2 levels in different cell types [7][8][9][10][11][12]. In vascular smooth muscle cells leptin induces MMP-2 expression via protein kinase C-dependent activation of NAD(P)H oxidase with subsequent activation of the ERK1/2/NF-kappa B pathways [8].…”
Section: Metabolic Parametersmentioning
confidence: 99%
“…It is well known that leptin, the product of the ob gene, is an endocrine hormone that regulates adipose tissue mass. In addition several in vitro and in vivo studies have revealed that leptin induces MMP-2 expression and activity [7][8][9][10][11][12]. This raises the question whether the marked effect of gelatinase inhibition by Tolylsam in a murine model of nutritionally induced obesity may be due not only to direct MMP inhibition, but also to an indirect effect via reduction of leptin and associated decrease in MMP-2 levels.…”
mentioning
confidence: 99%
“…Leptin treatment in human pediatric cardiomyocytes resulted in increased gene expression of MMP-2 and collagen type III and IV, while suppressing collagen type I mRNA, without affecting total collagen synthesis [10]. It also regulated MMP-2, TIMP-1, and collagen synthesis via p38 MAPK pathway in HL-1 murine cardiomyocytes [11]. The pro-fibrotic effects of leptin in hepatic and renal tissues have been extensively investigated in rodent-induced fibrosis models.…”
Section: Introductionmentioning
confidence: 98%
“…According to Hu et al 11 , moderately obese rats submitted to a high calorie diet have a high concentration of leptin. This hormone enhances the activity of the metalloproteinases MMP-229 29 and the mRNA expression of MMP-9 30 , enzymes responsible for collagen degradation. As the percentage of collagen in the diaphragm muscle was similar in the WD DJB and WD SHAM groups, it is suggested that the continued use of the cafeteria diet and the maintenance of post-DJB body weight maintained the leptin concentration and activity of matrix metalloproteinases high, leading to increased degradation of collagen in relation to its synthesis.…”
Section: ■ Discussionmentioning
confidence: 99%